Wczesne wspomaganie rozwoju dziecięcego głosu = Early support of children's voice development - Gebreselassie, Jolanta (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
Actions taken in the first years of life are important for proper voice emission. The work presents the development of the voice of new-borns and infants, and draws attention to the need for early, conscious interactions in this area. The next section presents exercises for use in working with children in the first months of life.
Keywords: noworodek; niemowlę; dziecko; głos; rozwój głosu; the new-born; infant; child; voice; voice development